The Effectiveness of Inquiry-Based Learning Models in Science Education: A Literature Review - Rizka Isnaeni; Nasywa Dwi Kamila; Nurmala Mustofa; Naya Mahdiyya Sari (Indonesian Publication Center, 2026)
The Inquiry-Based Learning (IBL) model is highly relevant to science education as it positions students as active learners who independently construct their knowledge. This study aims to identify and analyze the effectiveness of implementing the IBL model in science learning at the basic education level (elementary and junior high school). Employing a Systematic Literature Review (SLR) method that strictly adheres to the PRISMA protocol, this study analyzes 16 experimental and quasi-experimental articles published between 2015 and 2024. The synthesized results confirm that the application of IBL yields a significant positive impact on seven main learning achievement variables: critical thinking skills, scientific literacy, cognitive learning outcomes, conceptual understanding, science process skills, learning motivation, and collaboration skills. Nevertheless, this study also reveals that the effectiveness of inquiry heavily relies on students' cognitive readiness and the precision of the pedagogical design, making the guided inquiry approach highly essential. As a pedagogical implication, this research highlights the urgency of modifying IBL by integrating real-world environmental contexts and Socioscientific Issues (SSI) to overcome the stagnation of students' analytical scientific literacy in the future.